SCHOOL AND TEACHERS - ENVIRONMENT AND KEY FACTORFOR THE FORMATION OF SOCIAL SKILLS IN ADOLESCENTS - Daneva, Stanimira (E-Journal VFU, 2024)
The purpose of the study is to define socialization and analyze it as a process. Attention is drawn to the fact that, thanks to successful socialization, the young generations integrate into the world established by the previous generations, perceive the norms and established rules. The reasons for the emergence of differences in the degree of adaptation among adolescents, resulting from differences in the level of socialization, as well as the absence of an active life position in some of them, are being sought